Educational experiences and empowerment of Kaingang indigenous women: teacher training in rural education - Moises Marques Prsybyciem; Almir Paulo dos Santos; Rejane Fernandes da Silva Vier; Rosemari Monteiro Castilho Foggiatto Silveira (Universidade Federal do Norte do Tocantins, 2018)
This work aims to understand the context of Kaingang indigenous women in the Interdisciplinary Course in Rural Education: Natural Sciences - Licentiate of Federal University of Southern Border (UFFS), Campus Erechim, discussing aspects such as the educational experiences of female participation in construction of scientific knowledge and the empowerment of indigenous women with their inclusion in higher education. The methodology used has a qualitative approach of an interpretive nature and the research, in relation to the technical procedures, is bibliographical and documentary. The data were constructed using the Pedagogical Proposal of the Course (PPC), the observation of the experiences and the UFFS Academic Registry. The main results show that the Kaingangs indigenous women have a high degree of representation in the course in Rural Education in the training of teachers in the area of ​​Natural Sciences, thus realizing that the insertion of Kaingang women in higher education contributes to the construction of autonomy, empowerment and resistance of indigenous peoples. These results point to the importance of indigenous female participation in the construction of scientific knowledge and its re-signification, taking into account the social and cultural dynamics of the peoples of the countryside.